Follistatin could promote the proliferation of duck primary myoblasts by activating PI3K/Akt/mTOR signalling. Issue 5 (17th October 2014) - Li, Xinxin; Liu, Hehe; Wang, Haohan; Sun, Lingli; Ding, Fang; Sun, Wenqiang; Han, Chunchun; Wang, Jiwen
Abstract : FST (follistatin) is essential for skeletal muscle development, but the intracellular signalling networks that regulate FST-induced effects are not well defined. We sought to investigate whether FST promotes the proliferation of myoblasts through the PI3K (phosphoinositide 3-kinase)/Akt (protein kinase B)/mTOR (mammalian target of rapamycin) signalling. In the present study, we transfected the pEGFP-duFST plasmid and added PI3K and mTOR inhibitors to the medium of duck primary myoblasts. Then, we analysed the cellular phenotypic changes that occurred and analysed the expression of target genes. The results showed that FST promoted myoblast proliferation, induced the mRNA expression of PI3K, Akt, mTOR, 70-kDa ribosomal protein S6K (S6 kinase) and the protein expression of phospho-Akt (Thr 308 ), mTOR, phospho-mTOR (serine 2448), phospho-S6K (Ser 417 ), inhibited the mRNA expression of FoxO1, MuRF1 (muscle RING finger-1) and the protein expression of phospho-FoxO1 (Ser 256 ). Moreover, we found that the overexpression of FST could alleviate the inhibitory effect of myoblast proliferation caused by the addition of LY294002, a PI3K inhibitor. Additionally, the overexpression of duck FST also relieved the inhibition of myoblast proliferation caused by the addition of rapamycin (an mTOR inhibitor) through PI3K/Akt/mTOR signalling. In light of the present results, we hypothesize that duck FST could promote myoblast proliferation, which is dependent on PI3K/Akt/mTOR signalling.